Faraway tree adventure - Blyton, Enid (London Hodder Children Books, 2021)
A full-colour short story taken from the world of the Magic Faraway Tree. Perfect for new readers. Discover the magic!It's Beth's birthday, so everyone is delighted when the Land of Birthdays arrives at the top of the Faraway Tree. It's time for the most magical party they've ever had!The stories about the Magic Faraway Tree have been entertaining children for more than 80 years. Now these colour short stories offer a great way for young new readers to discover the adventures of Silky, Moon-Face, the Saucepan Man and all of their friends in the Enchanted Wood. Also available in this short story series: A Faraway Tree Adventure: The Land of Birthdays A Faraway Tree Adventure: The Land of Magic Medicines A Faraway Tree Adventure: The Land of Do-As-You-Please A Faraway Tree Adventure: The Land of Goodies A Faraway Tree Adventure: In Santa Claus's Castle A Faraway Tree Adventure: The Land of Toys A Faraway Tree Adventure: The Land of Dreams A Faraway Tree Adventure: The Land of Silly School A Faraway Tree Adventure: The Land of Enchantments A Faraway Tree Adventure: Joe and the Magic Snowman
Keywords: Children Books